Pemberdayaan Pelaku Usaha Gabah Kopi di Gabah Kopi Atep Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Nurhayati, Nurhayati; Purwanti, Yanti; Fauzi, Teddy Hikmat (Jurnal Pengabdian Tri Bhakti, 2020)
Pangalengan a district in Bandung Regency, West Java Province. Pangalengan is located in the south of Bandung City and is famous for various tourist objects such as Situ Cileunca, tea plantations and Cibolang hot springs. Pangalengan is also known as an area of agriculture, livestock and plantations. There are several tea plantations managed by PTPN. Pangalengan is also an area for producing cow's milk, livestock and milk processing in the Pangalengan area. Another potential that is currently growing rapidly is coffee plantations. Citiis Village, which is located in Warnasari Village, Pangalengan District, is one of the villages that produces Arabica coffee. Most of the farmers in Citiis village grow coffee, because the price of coffee cherries or what is called logs is higher than vegetables and tea. Common problems faced by partners are marketing management, production management and financial management. The priority problem of partners is the Production Aspect where the Milling Machine (pulper) is damaged so that it cannot grind coffee to separate the beans and skins and the partner cannot produce more coffee grain. As well as the capital aspect, currently partners do not get capital assistance from any banking or non-financial institution due to limited knowledge about recording or bookkeeping as a condition for borrowing capital. The solution offered is to repair the damaged coffee milling machine (pulper) so that it can function again, as well as provide training in making simple financial reports so that partners can lend to banks or other non-financial institutions to increase capital in developing their business.